Terms associated with refractory materials - 8096 British Standards Institution (London : British Standards Institution, 1990)
Part 1 General and manufacturing -- part 2 Applications in the coke, glass, cement and other non-metallurgical industries -- part 3 Applications in the metallurgical indutries